Spatiotemporal evolution of shorelines in Shenzhen Bay (1986–2020): contrasting impacts of rapid urbanization in Shenzhen and natural processes in Hong Kong - He, Qiule; Wu, Xiaojun; Huang, Yilong; Ma, Enze; Yang, Jingwei; Wang, Jian (Frontiers in Marine Science, 2025)
Shoreline dynamics are a critical concern for coastal regions worldwide, particularly in economically vital estuarine deltas with dense populations and infrastructure. Long-term monitoring is essential for understanding responses to both natural and anthropogenic forces and for informing sustainable coastal management. This study analyzes the spatiotemporal evolution of shorelines in Shenzhen Bay, China, over 35 years (1986–2020) using Landsat-derived shorelines at five-year intervals. Rate-of-change statistics were calculated using the Digital Shoreline Analysis System (DSAS). Results show substantial morphological changes: artificial shorelines increased by 120%, biological shorelines by 89%, sandy shorelines decreased by 64%, and total shoreline length increased by 9% overall. The bay area decreased by 18.5% due to reclamation. More than half (54.8%) of Net Shoreline Movement (NSM) values fall within 0–1000 m, but spatial patterns reveal marked contrasts between Shenzhen and Hong Kong: Shenzhen transects show a much greater mean displacement (965.13 m) than Hong Kong (81.65 m). End Point Rate (EPR) analysis confirms faster change rates in Shenzhen (28.10 m/a) compared with Hong Kong (2.37 m/a). Analysis of driving forces indicates that while sea level rise (1.85 mm/a) and sediment accumulation contributed to observed changes, anthropogenic activities—particularly land reclamation and channel engineering—were the dominant factors. These findings highlight the urgent need for integrated coastal management strategies to balance development and ecosystem conservation in rapidly urbanizing estuarine environments.